Pengaruh Daya Tarik Wisata dan Citra Destinasi Terhadap Minat Berkunjung Kembali Pada Objek Wisata Air Terjun Kerta Gangga - Ningsih, Tri Muria Ayu; Sagir, Junaidi (Postgraduate, University of Mataram, 2024)
This research aims to determine the influence of tourist attraction and destination image on interest in revisiting the Kerta Gangga Waterfall tourist attraction. The type of research used is associative research with a quantitative approach. Research data collection uses questionnaires. The population in this study were all tourists who had visited and were interested in revisiting the Kerta Gangga Waterfall tourist attraction with a sample size of 100 respondents with a sampling technique using non-probability sampling with a purposive sampling method. The data analysis used was Multiple Linear Regression using SPSS Version 24. The results of the analysis showed that: Tourist Attraction, Destination Image had a positive and significant effect on Interest in Returning to the Kerta Gangga Waterfall Tourist Attraction